The gradual disappearance and re-appearance of yield drop by modulating the pre-strain history in a new zirconium alloy: Dislocation decomposition and recombination. (November 2020) - Shi, Huigang; Li, Jiuxiao; Mao, Jianwei; Lu, Weijie
Abstract: We report an interesting phenomenon in a new zirconium alloy where the yield drop gradually disappeared and re-appeared by modulating the pre-strain history. The initial yield drop is caused by the lack of mobile dislocations in crystal, and increased density of mobile dislocations introduced by pre-strain (< 1%) lead to the disappearance of yield drop. The latter one can be explained by the recombination of partial dislocations. That is, the climb-dissociated partials introduced by pre-strain deformation (> 9%) recombine onto the same prism plane to regain its moving ability, resulting in the re-appearance of yield drop. Graphical abstract: Image, graphical abstract